2022
DOI: 10.1039/d1ma00914a
|View full text |Cite
|
Sign up to set email alerts
|

Increased performance of an all-organic redox flow battery model via nitration of the [4]helicenium DMQA ion electrolyte

Abstract: Symmetrical non-aqueous organic redox flow batteries are highly promising systems for electrochemical energy storage. A higher solubility and energy density of a previously described robust ROM was obtained by straightforward nitration of its core.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 56 publications
(85 reference statements)
0
12
0
Order By: Relevance
“…Their first study involved the plain carbenium ion, which is able to reduce to a neutral radical, and oxidize to a dicationic radical state with a ∆E of 2.12 V, paired with high diffusion coefficients (9.4 and 9.9 × 10 −6 cm 2 s −1 , respectively). Although the dicationic radical of the plain carbenium could not be isolated, a follow-up study with a nitro-substituted carbenium exhibited increased stability to all redox-states, including the doubly reduced form, allowing for an impressive 3.02 V OCV (Figure 13) [114]. The updated design also yielded a large increase in solubility from 32 to 154 mM with the nitro-substituent, leading in turn to higher energy densities also (9.25 W h L −1 versus the previous 1.84 W h L −1 , with 12.5 W h L −1 upon double reduction).…”
Section: Bipolar Electrolytesmentioning
confidence: 99%
See 1 more Smart Citation
“…Their first study involved the plain carbenium ion, which is able to reduce to a neutral radical, and oxidize to a dicationic radical state with a ∆E of 2.12 V, paired with high diffusion coefficients (9.4 and 9.9 × 10 −6 cm 2 s −1 , respectively). Although the dicationic radical of the plain carbenium could not be isolated, a follow-up study with a nitro-substituted carbenium exhibited increased stability to all redox-states, including the doubly reduced form, allowing for an impressive 3.02 V OCV (Figure 13) [114]. The updated design also yielded a large increase in solubility from 32 to 154 mM with the nitro-substituent, leading in turn to higher energy densities also (9.25 W h L −1 versus the previous 1.84 W h L −1 , with 12.5 W h L −1 upon double reduction).…”
Section: Bipolar Electrolytesmentioning
confidence: 99%
“…A1 = N-methylphthalimide [96,97], A2 = quinoxaline [98], A3 = anthraquinone [99], A4 = benzophenone [100], A5 = viologen [101,102], A6 = azobenzene [103,104]. B1 = N-ferrocenylphthalimide [105], B2 = 1,4-diaminoanthraquinone [106,107], B3 = thianthrene [108], B4 * = 2,2,6,6-tetramethyl-1-piperidinyloxy (TEMPO) in ionic liquid [109], B5 = 2-phenyl-4,4,5,5-tetramethylimidazoline-1-oxyl-3-oxide [110,111], B6 = 1,5-diphenyl-3-isopropyl-6-oxo-verdazyl [36], B7 = 1,2,4-benzotriazin-4-yl [112], B8 = dimethoxyquinacridinium [113,114], C1 = 2,2,6,6-tetramethyl-1-piperidinyloxy (TEMPO) [96], C2 = dialkoxybenzene [98,[115][116][117][118][119], C3 = ferrocene [120][121][122], C4 = phenothiazine [99], C5 = triarylamine [123].…”
Section: Introductionmentioning
confidence: 99%
“…One promising recent design strategy involves the direct π-conjugation of typical anode and cathode active species, [29][30][31]42 where such electronic coupling causes synergistic benefits in cell potentials compared to the parent molecules. 29,30 Most intrinsically bipolar molecules are based on oneelectron redox events (one-electron oxidation and one-electron reduction), 14,18,[26][27][28][29][30][31][32][33][34][35]38,39 which severely limits energy densities (the product of cell voltage, active material concentration, and number of electrons transferred). Indeed, a previous analysis has suggested that for nonaqueous organic RFBs to be cost-effective, active material concentrations as high as 4−5 M would be needed (assuming one-electron processes and cell voltages of 3 V).…”
mentioning
confidence: 99%
“…), such that the low and high redox potential units are discrete and largely have the properties of their respective unbridged parent structures. The other is intrinsic, which features a conjugated framework with electronic communication between atoms associated with reduction and those associated with oxidation (including cases where those atoms are largely identical). ,, Intrinsically bipolar molecules therefore offer advantages in term of atom economy but are more challenging to design than artificial alternatives. One promising recent design strategy involves the direct π-conjugation of typical anode and cathode active species, , where such electronic coupling causes synergistic benefits in cell potentials compared to the parent molecules. , …”
mentioning
confidence: 99%
See 1 more Smart Citation